ESTUDO DE CASO: O ATENDIMENTO DO PROCESSO DE GESTÃO AMBIENTAL, ATRAVÉS DE UM SISTEMA INTEGRADO DE GERENCIAMENTO DE RESÍDUOS SÓLIDOS INDUSTRIAIS, SIR - Quinteiro, Agmar de Carvalho (2004)
Duque de Caxias Refinery, REDUC, situated at Duque de Caxias Town in an area of 13 million m2 was inaugurated at the sixty decade and contemplates a large industrial complex established by energy conception, transference and stocking systems. The complex still fabricates 54 product types from petroleum refine as lubricants, paraffins, fuels and derivates to petrolchemical industries. The production of these composts causes interactions with the environment that can prejudice air, water and soil qualities, characterizing REDUC such as a potentially polluter industry. To attend the directives of Security, Environment and Health Politic, SMS, REDUC has been certificated in ISO statute, determining this way an Environmental Gestation System that has adopted as one of its instrument Integrated Residues Gestation System, SIR. SIR does a trajectory accompaniment of residues from 48 unities equivalents to medium size industries. Through a data bank, industrial residues creation could be proceeded more efficiently, with the treatment to recover energy and the use of resources that produces the minimum quantities of these residues or that are reusables. This improvement in residues creation monitoring has also made possible reduction in its peril grade, adaptations in handling, packaging, transport, treatment and final destination, measurements of the volume and of generating sources, besides best environmental compromising of the workforce, more efficient communication among the managers, optimization of the inventory process emission and more warranty in obligated executions of the legal and subscript requirements for REDUC. The functionalities meditated by SIR are developed for the atmosphere Intranet of PETROBRAS/REDUC and still include: - Identification of the residues through bar codes; - Information to the technicians of SMS in the occurrence places of sinister; - Alert systems for storage activities and transport of the residues; - Activities determinations in the forecast of residues generation; - Maps and routes impression for residues transport; - Impression of residues originating manifesto by interaction with the Residues Inventory System of FEEMA.